P1741TACROLIMUS FAST METABOLIZERS SHOW A HIGHER PROGRESSION OF INTERTITIAL FIBROSIS AND TUBULAR ATROPHY DURING THE FIRST YEAR AFTER RENAL TRASPLANTATION. (6th June 2020) - Chamoun Huacon, Betty; Torres, Irina; Gabaldon, Alejandra; Toapanta, Néstor; Sellares, Joana; Perello, Manel; Moreso, Francesc; Seron Micas, Daniel
Abstract: Background and Aims: Fast tacrolimus metabolizers (expressed as the blood concentration/ dose ratio; C / D; ng / mL * mg) showed poorer renal function at 2 years, a higher incidence of nephrotoxicity and BK polyomavirus infection. Greater variability of tacrolimus trough levels (CV) from six to twelve months is associated with the appearance of HLA antibodies, interstitial fibrosis / tubular atrophy (IFTA) progression and allograft loss. We evaluate the relationship between C / D, CV and IFTA progression. Method: We evaluated a cohort of 87 low immunological risk renal transplants treated with prolonged-release tacrolimus, mycophenolate mofetil and steroids. We analyzed paired protocol biopsies at 4 and 18 months. Biopsies were evaluated according to the Banff classification and the progression of IFTA was defined as the difference of ci + ct score> 0 between 18 and 4 months. The C / D ratio was calculated as the average of the value recorded at 3, 6 and 12 months of follow-up. The tacrolimus CV between 6 and 12 months was calculated using all the available determinations. Results: IFTA progression was observed in 36 cases (41%). In the univariate analysis, it was found that the progression of IFTA was associated with the ci + ct score at 4 months (0.92 ± 0.94 for progressors vs. 1.89 ± 1.26 not progressors, p = 0.0003), and with the average of the C / D ratio (1.70 ± 0.73 for progressors vs. 2.28 ± 1.25 not progressors; p = 0.0144, table 1). An independent association between the C/D ratio and the progression of IFTA was observed in the multivariate analysis (OR: 0.42; 95% CI: 0.22-0.82, p = 0.027). Conclusion: The results of our work suggest that fast tacrolimus metabolizers (lower C / D ratio) are more susceptible to the nephrotoxic effect of tacrolimus.